The impact of ESG and the institutional environment on investment efficiency in China through the mediators of agency costs and financial constraints - Zhao, Donghui; Wan Sallha, Yusoff; Mohd Fairuz, Md Salleh; Ngan, Sue Lin; Ainul Huda, Jamil; Mohd Juraij, Abd Rani; Mohd Shahidan, Shaari (Elsevier Ltd., 2025)
This study examines the impact of environmental, social, and governance (ESG) performance on corporate investment efficiency in China, focusing on underexplored dynamics in emerging markets. Using data from 3380 non-financial Chinese firms (2010–2021) and a fixed-effects panel regression model, we explore how ESG influences investment efficiency through the mediating roles of agency costs and financial constraints. Findings reveal that high ESG performance reduces agency costs and eases financial constraints, enhancing investment efficiency. Additionally, we assess the moderating effect of China's institutional environment, characterized by four indicators: marketization, financial development, government intervention, and regulatory quality. Results show that ESG's positive impact on investment efficiency is stronger in regions with more robust institutional frameworks. This study underscores the importance of adapting ESG strategies to varied institutional contexts, offering valuable insights for policymakers and corporate leaders seeking to promote sustainable growth across diverse regions.